PEG-crosslinked-chitosan hydrogel films for in situ delivery of Opuntia ficus-indica extract. (15th July 2021) - Catanzano, O.; Gomez d'Ayala, G.; D'Agostino, A.; Di Lorenzo, F.; Schiraldi, C.; Malinconico, M.; Lanzetta, R.; Bonina, F.; Laurienzo, P.
Graphical abstract: Highlights: Opuntia ficus-indica (OPU) extract was loaded within PEG- crosslinked chitosan films. The prepared films showed swelling and vapor transmission rate suitable as wound dressings. At a given composition, the Young's modulus of films is close to that of human skin. Release of OPU was higher from films at low OPU load. Low OPU content films showed the best tissue repairing activity. Abstract: In the present study, chitosan-based wound dressings loaded with the extract of Opuntia ficus-indica (OPU) were prepared. OPU is known for its capability to accelerate skin injury repair. Chitosan (Ch) was crosslinked with a low molecular weight diepoxy-poly(ethylene glycol) (diePEG), and hydrogel films with different Ch/PEG composition and OPU content were prepared by casting. The occurrence of crosslinking reaction was confirmed by FTIR spectroscopy. FTIR and DSC analysis suggested that ionic interactions occur between chitosan and OPU. Tensile tests evidenced that the crosslinking caused a decrease of Young's modulus, which approaches the value of the human skin modulus. Swelling characteristics, water vapor transmission rate, and release kinetics demonstrated that these films are adequate for the proposed application. Finally, a scratch test on a keratinocytes monolayer showed that the rate of cell migration in the presence of OPU-loaded samples is about 3-fold higher compared to unloaded films, confirming the repairing activity of OPU.